Pharmacology mind maps for medical students and allied health professionals - Bhandari, Prasan R. (Boca Raton, FL : CRC Press/Taylor & Francis, 2020)
Pharmacology Mind Maps is meant as a concise companion for the pharmacology students, enabling them to revise the subject in a short time through the innovative and effective technique of mind maps, after understanding the subject from a standard reference textbook. This handy manual provides the subject information in a condensed form, helping in last minute revision. Mind mapping is slowly taking over traditional methods and techniques and is explored extensively for a subject like pharmacology which is both an essential as well as a difficult subject to master for a medical student. This book will thus help the students to read, revise and recollect the subject easily and rapidly.
Part I: General pharmacology. Definitions, drug nomenclature, and sources of drugs -- Routes of drug administration -- Pharmacokinetics and applied aspects -- Pharmacodynamics -- Adverse drug reactions -- New drug approval process and clinical trials -- Part II: Autonomic nervous system (ANS) pharmacology. Introduction to ANS -- Cholinergic system and drugs -- Anticholinergics -- Skeletal muscle relaxants -- Adrenergic system and drugs -- Alpha-adrenergic blocking agents (a blockers) -- Beta-adrenergic blockers ([beta] blockers) -- Part III: Cardiovascular pharmacology. Antihypertensives -- Calcium channel blockers, drug treatment of angina pectoris, and myocardial infarction -- Cardiac glycosides and treatment of cardiac failure -- Antiarrhythmics -- Diuretics and antidiuretics -- Pharmacotherapy of shock -- Part IV: Central nervous system (CNS) pharmacology. Introduction to CNS and alcohol -- Sedative hypnotics -- Antiepileptics -- Antidepressants -- Mood stabilizers and lithium -- Antipsychotics -- Drug treatment of Parkinsonism and Alzheimer's disease -- General anesthetics (GA) -- Local anesthetics (LA) -- Opioid analgesics -- CNS stimulants/drugs of abuse -- Part V: Autacoid pharmacology. Autacoids, histamine and antihistaminics -- 5-Hydroxytryptamine agonists and antagonists and drug treatment of migraine -- Eicosanoids and leukotrienes -- Nonsteroidal anti-inflammatory drugs (NSAIDs) -- Drugs used in rheumtoid arthritis and gout -- Part VI: Respiratory pharmacology. Drugs used in the treatment of bronchial asthma and chronic obstuctive pulmonary disorders (COPD) -- Drugs used in the treatment of cough -- Part VII: Hematological pharmacology. Hematinics -- Hemostatic agents -- Anticoagulants -- Antiplatelet agents -- Thrombolytics (fibrinolytics) and antifibrinolytics -- Hypolipidemic drugs -- Part VIII: Gastrointestinal pharmacology. Drug therapy of peptic ulcer and GERD -- Emetics and antiemetics -- Drug treatment of constipation, treatment of IBS, and IBD -- Drug treatment of diarrhea -- Part IX: Endocrine pharmacology. Hypothalamic and pituitary hormones -- Thyroid hormones and antithyroid agents -- Estrogen, progestins, and hormonal contraceptives -- Androgens and anabolic steroids -- Corticosteroids -- Insulin and oral antidiabetic agents -- Agents affecting calcium balance -- Drugs acting on uterus -- Part X: Chemotherapy. General chemotherapy -- Beta-lactam antibiotics -- Sulfonamides -- Chemotherapy of urinary tract infections and sexually transmitted diseases -- Quinolones -- Macrolides -- Broad-spectrum antibiotics - Tetracyclines and chloramphenicol -- Aminoglycosides -- Miscellaneous antibiotics -- Chemotherapy of tuberculosis (TB) -- Chemotherapy of leprosy -- Chemotherapy of malaria -- Drugs for amebiasis/pneumocystosis/leishmaniasis/trypanosomiasis -- Antiviral drugs -- Antifungal drugs -- Anthelmintics -- Antiseptics and disinfectants -- Cancer chemotherapy -- Part XI: Miscellaneous. Chelating agents -- Immunosuppressants and immunostimulants.
Chiefly charts.
OCLC-licensed vendor bibliographic record.
Keywords: Pharmacology -- Examinations -- Study guides; Mnemonics; MEDICAL / Nursing / General; MEDICAL / Pharmacology